1996
DOI: 10.1017/s0022143000003531
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance of White Glacier, Axel Heiberg Island, N.W.T., Canada, 1960–91

Abstract: White Glacier is a valley glacier at 79.5°N with an area of 38.7 km2. Its mass balance has been measured, over 32 years with a 3 year gap, by standard techniques using the stratigraphic system with a stake density of the order of one stake per km2. Errors in stake mass balance are about ±(200–250) mm, due largely to the local unrepresentativeness of measurements. Errors in the whole-glacier mass balanceBare of the same order as single-slake errors. However, the lag-1 autocorrelation in the time series ofBis ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Dowdeswell et al (1997) similarly found that Scandinavia had a stronger mass balance response from the relatively more variable precipitation rate for other Arctic glaciated regions. Arctic Canada has no apparent precipitation sensitivity yet exhibits the strongest T regional Warm Season sensitivity (Correlation=−0.760), consistent with low precipitation rates (under 300 mm yr −1 , Cogley et al 1996, Dyurgerov 2002) based on the reanalysis product. Arctic Canada snow accumulation rates are similar to other High Arctic glacier regions.…”
Section: Land Icesupporting
confidence: 58%
“…Dowdeswell et al (1997) similarly found that Scandinavia had a stronger mass balance response from the relatively more variable precipitation rate for other Arctic glaciated regions. Arctic Canada has no apparent precipitation sensitivity yet exhibits the strongest T regional Warm Season sensitivity (Correlation=−0.760), consistent with low precipitation rates (under 300 mm yr −1 , Cogley et al 1996, Dyurgerov 2002) based on the reanalysis product. Arctic Canada snow accumulation rates are similar to other High Arctic glacier regions.…”
Section: Land Icesupporting
confidence: 58%
“…2.1. Glacier and ice cap climatic mass balance measurements Annual surface mass balance from 61 glaciers and ice caps located between latitude 55°and 79°latitude are updated after Mernild et al (2013), using data from World Glacier Monitoring Service (WGMS 2017), Dyurgerov and Meier (2005), Cogley et al (1996), and through personal correspondence from principle investigators (see supplementary table 1, available online at stacks.iop.org/ ERL/13/125012/mmedia). Each mass balance record represents the 'specific', i.e.…”
Section: Datamentioning
confidence: 99%
“…There are four long‐running glacier SMB records from the CAA [the Devon Ice Cap (Burgess and Koerner, ), Meighen Ice Cap (Burgess, ), Melville Ice Cap (Burgess, ) and the White Glacier (Cogley and Ecclestone, )] (Figure ). These records begin in 1961, 1960, 1963 and 1960, respectively, and end in the 2011 mass balance year (measured in the spring of 2012).…”
Section: Datasetsmentioning
confidence: 99%